Analysis of School Participation Rates and Their Implications on Poverty Level in Mediation of Per Capita Income in Hulu Sungai Utara Regency - Akhmad Abdurahman; Nahdiatuzzakiah; Semuel Risal (East Asian Journal of Multidisciplinary Research, 2022)
Poverty is the inability to meet the minimum standard of basic needs caused by various factors such as low access to education. This study aims to analyze the effect of school enrollment rates on per capita income, the effect of school enrollment rates and per capita income on the percentage of poor people, and the effect of school enrollment rates on the percentage of poor people through per capita income. This study uses a quantitative descriptive approach. Sampling in this study uses purposive sampling. The unit of analysis is data on School Participation Rate (APS), Percentage of Poor Population, and income per capita (GDP per capita) in Hulu Sungai Utara Regency. Furthermore, the data were analyzed using descriptive analysis and inferential analysis. The results showed that there was no significant effect of the school enrollment rate on per capita income, there was a significant effect of the school enrollment rate on the percentage of the poor population, and there was no negative and statistically significant effect of the per capita income on the percentage of the poor population, there was a negative mediating effect of the variable number School participation through per capita income to the percentage of poor people.